The Contribution of Residential Segregation to Racial Income Gaps: Evidence from South Africa - (:unkn) unknown (My University, 2020)
Persistent racial income disparities cannot only be explained by differences in socio-economic characteristics. In this paper, we contend that local segregation should be an essential component of the determination of socio-ethnic income gaps using the contemporary White/African gap in South Africa. First, we complete Mincer wage equations with an Isolation index. Second, we decompose the income gap distribution into detailed composition and structure components. Third, we explore the heterogeneity of segregation effects along three theoretical lines: racial preferences, labor market segmentation, and networks effects. Segregation is found to be the main contributor of the structure effect, ahead of education and experience, and to make a sizable contribution to the composition effect. Moreover, segregation is detrimental to incomes at the bottom of the African distribution, notably in association with local informal job-search networks, while it is beneficial at the top of the White distribution. Only minor influences of racial preferences and labor market segmentation are found. Specific subpopulations are identified that suffer and benefit most from segregation, including for the former, little educated workers in agriculture and mining, often female, immersed in their personal networks. Finally, minimum wage policies are found likely to attenuate the segregation’s noxious mechanisms.
Keywords: African Research